Cultivating Climate Solutions: Agroforestry’s Potentials and Roles in North Kalimantan’s REDD+ Program - Sutrisno, Adi; Agang, Wahyu; Hartono, Tjahjo Tri; Sayaza, Mas Davino (Ilomata International Journal of Social Science, 2024)
Agroforestry in North Kalimantan offers a promising avenue for balancing community livelihoods with carbon sequestration, crucial for the REDD+ initiatives. This paper examines the potential of agroforestry in North Kalimantan to support the REDD+ program, addressing both environmental sustainability and socio-economic development. Through field observations and interviews across four regencies and one city in North Kalimantan province, various agroforestry practices were identified, including improved fallows, alley cropping, scattered trees on cropland, living fences, and silvofishery. Challenges such as cultivation practices, post-harvest processing, market access, and financing were also explored. Three potential agroforestry models were proposed to enhance carbon capture while promoting local economic resilience. The paper underscores the importance of further research and community involvement to refine and expand these agroforestry approaches, offering hope for both local prosperity and global carbon reduction efforts.